FRI0523 Short-term efficacy and safety of new biological agents targeting the IL-6, IL-12/23 and IL-17 pathways for active psoriatic arthritis: a network meta-analysis of randomised controlled trials. (15th June 2017) - Dongze, W; Jiang, Y; Tam, L-S
Abstract : Background: IL-6, IL-12/23 and IL-17 inhibitors have been found to be highly effective for both skin and joint manifestations of psoriatic arthritis (PsA). Nonetheless, reliable evidence of the comparative benefits and harms for these interventions is absent for treatment selection in daily practice. Objectives: To investigate the comparative efficacy, safety and tolerability of IL-6, IL-12/23 or IL-17 inhibitors and the proportion attributable to overall treatment for patients with active PsA. Methods: Randomized controlled trials (RCTs) evaluating the efficacy, safety and tolerability of IL-6, IL12/23 or IL17 inhibitors at weeks 24 were identified by a comprehensive systematic literature review (PROSPERO 2016: CRD42016048166). Quality of evidence was assessed following the Grading of Recommendations, Assessment, Development and Evaluations (GRADE) approach. Treatment effects were evaluated based on the intention-to treat efficacy rates (ACR20, ACR50), safety parameters (any adverse effect [AE], serious adverse effect [SAE]) and tolerability (discontinuation due to AE [DAE]). Pair-wise meta-analyses and Bayesian network meta-analyses using the random-effects model were performed to estimate pooled odds ratios (ORs) and 95% credible interval (CrI). A subgroup analysis was performed to investigate the effects of prior anti-TNF exposure on the efficacy of ustekinumab and secukinumab. Results: Six trials were identified which included 2411 participants and 11 treatments. All trials were of generally high quality according to Cochrane compliant rules and GRADEpro assessment. Direct comparisons of each biologic showed that secukinumab, ustekinumab and ixekizumab demonstrated superior efficacy over placebo with respect to all efficacy outcomes (ACR20 and ACR50). Regarding safety and tolerability, ixekizumab has a higher incidence of adverse events while ustekinumab were more tolerable compared with placebo. Mixed treatment comparisons showed that secukinumab (300mg monthly) had the highest efficacy in achieving ACR20 and ACR50; whereas clazakizumab (200mg monthly), ustekinumab (45mg 12 weekly), secukinumab (150mg monthly) had the lowest probability of having AE, SAE, DAE, respectively. Considering the overall risk-benefit profile of IL-6, IL12/23, IL17 inhibitors in the treatment of active PsA, secukinumab (150mg monthly) may offer an optimal balance for active PsA patients (Figure 1 ). When considering ACR 20 response, subgroup analysis revealed that anti-TNF naïve patient respond significantly better than placebo for all dosages of secukinumab and ustekinumab used. In contrast, only higher dose of secukinumab and ustekinumab were significantly more effective than placebo in anti-TNF failure patient. Conclusions: In conclusion, from the available evidence, secukinumab and ustekinumab were found to be the safest and most efficacious short-term treatments for active PsA amongst all the new biologics targeting the IL-6, IL-12.23 and IL-17 pathways. Acknowledgements: Thank all colleagues working in the Division of Rheumatology, Department of Medicine and Therapeutics, The Prince of Wales Hospital, The Chinese University of Hong Kong. Disclosure of Interest: None declared